REVELATION, SACRED SCRIPTURE AND THE CHURCH AS TRADITION: A Dynamic Understanding of Tradition in Dei Verbum - Pathrapankal, Joseph (Asian Horizons, 2013)
The Dogmatic Constitution on Divine Revelation is one of the most important documents of Vatican II, precisely because of its significance for the life of the Church insofar as all its sixteen documents depend on the faith commitment of the Church to the word of God to the humankind, and it is this truth which the Council has clearly spelled out in this Constitution. At the same time, it is to be remembered that this is the one document which had a dramatic history behind it from the time it was introduced in the Council in 1962 till it was finally voted on in November 1965. The original schema was largely rewritten. The original first chapter, “Two Sources of Revelation,” meaning thereby Scripture and Tradition, was replaced by two chapters, on revelation itself and on its transmission, through which Scripture and Tradition were not understood as separate sources. The entire approach to the subject was from a biblical and historical perspective. The first two chaptersdeal with the reality of revelation in which a personal God enters into a dialogue with the humankind, which is transmitted to the following generations through a historical process. The response to this dialogue is known as faith which is much more than an intellectual assent to some divine propositions. It is a commitment to a personal God who in manifold ways reveals himself and his plans to the humankind. The following chapters are devoted to the understanding of divine inspiration and interpretation of the Bible as well as the analysis of the Old and New Testaments and the role of the Sacred Scripture in the life of the Church.